Product Marketing Strategy Analysis Based on Digital Marketing on Customer Satisfaction - Hidayat, Lembayung Sarip; Ridwan, Muhamad; Purnamasari, Deby (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2022)
Starbucks is one of the pioneers of coffee that has been famous for a long time because it has existed in various countries in the world. Starbucks uses a digital marketing strategy to reach customers who are its target market. Digital marketing is used to promote digitally through social media. This study aims to analyze the improvement of Starbucks product marketing with digital-based techniques. The method used in this study uses digital marketing strategies, namely branding, promotion and influencers marketing. The results of this study used quantitative which distributed questionnaires to respondents. The results of this study indicate that digital marketing has a positive effect on increasing sales. The researcher also distributed several questionnaires to the respondents who were Starbucks customers.